Who asks for vasectomy reversal and why?. Issue 6340 (14th August 1982) - Howard, G
Abstract : Of the 76 men requesting reversal of vasectomy who were interviewed at Charing Cross Hospital between June 1978 and September 1981, 31 were still married. These men had decided to have a vasectomy during a crisis-a recent pregnancy or financial stress being the commonest reason. Most wanted another child but others wished to be "put back to normal, " and a few hoped reversal would help their marriage. Forty-five (59%) were divorced or separated and felt disadvantaged in courtship or remarriage by being infertile, many wives or partners being "desperate" for a pregnancy. A greater number of requests for reversal came from men who had been under 35 at the time of vasectomy and who were more likely to have been divorced, especially if there had been a teenage pregnancy. The risks of regret after sterilisation appear to relate to immaturity at the time of the vasectomy and to be as great for young men as for young women.